PLANNING OF RELIGIOUS TOURISM AREA OF GUS DUR TOMB INTEGRATED WITH REGIONALISM STRATEGY - Jayanata Putra; Dewi Septanti; Murni Rachmawati (Journal of Islamic Architecture, 2022)
Uncontrolled tourism development makes an area develops unevenly and causes changes of function that can harm the surrounding community. Thus, integration in an area is needed to form urban area plans. The development of tourist areas cannot be separated from the change of function that leads to the changes in areas that develop unevenly. For example, a change of lifestyle makes people initially gathered in open spaces move to areas with certain interests. So, the integration between spaces is an important concern in the scope of region development. These corridors can become open spaces that improve the quality of tourist areas. This research aims at identifying the potential development of the religious tourism area of Gus Dur Cemetery in Jombang City with a regionalism approach. It includes activities, facilities, and several symbols that increase the value of the place. The research method employed logical argumentation on which the research relies on argument as a reference in aspects and results of research. The data collection techniques are interviews, observations, cognitive mapping, and literature studies. This study shows some activities that need to be developed; providing an open space to support the community activities, providing facilities that make the value of a tourist area can increase economically, developing new symbols, developing religious tourism areas, and arranging landscapes.